SCIENTIFIC STUDIES OF GLOBAL WARMING, CLIMATE CHANGE, GLACIER MELTING AND SALMON PROTECTION - Hung-ping Tsao; Lawrence K Wang; Nai-Yi Wang; Lawrence K. Wang; Mu-Hao Sung Wang; Josephine O. Wong (Lenox Institute Press, PO Box 405, Newtonville, NY, 12128-0405, USA, 2019)
Wong, Josephine O., Wang, Nai-Yi, Wang, Lawrence K. and Wang, Mu-Hao Sung (2019). Scientific studies of global warming, climate change, glacier melting and salmon protection. In: "Evolutionary Progress in Science, Technology, Engineering, Arts, and Mathematics (STEAM)", Wang, Lawrence K. and Tsao, Hung-ping (editors). Volume 1, Number 9, September 2019; 110 pages. Lenox Institute Press, Newtonville, NY, 12128-0405, USA. No. STEAM-VOL1-NUM9-SEP2019; ISBN 978-0-9890870-3-2. --- ABSTRACT: Scientific studies of global warming, climate change, glaciers melting and salmon protection conducted by international researchers are reviewed, presented and discussed. The topics covered in this book chapter include: technical terminologies, climate change, global warming, main contributors to greenhouse gases, global warming potential and its limitations, absorption of heat by carbon dioxide, rising temperature trend in the environment, land temperature rise, ocean temperature and its water level rise, glacier melting, glacier protection, tidewater glaciers, Glacier Bay National Park and Reserve, Mendenhall Glacier, Mendenhall Lake, salmon protection, salmon life cycle, fire frequency, carbon dioxide stabilization, actions for environmental protection, and Macaulay Salmon Hatchery, Alaska, USA.